URGENSI KESEHATAN MENTAL DALAM PENDIDIKAN ISLAM - Sri Mulyani; Muhamad Habib (STAI Sufyan Tsauri Majenang, 2020)
Understanding mental health is a problem that must be understood by all groups, especially education circles, because maintaining mental health is one of the supporting factors for the success of Islamic education. Mental health is an individual's healthy state so that he can adjust to develop all the potential in him for himself, other people and the environment so that it can be useful for himself and the surrounding nature. This study aims to determine the urgency of mental health in Islamic education. This research is a library (Library Research), data collection by the documentation method that is searching for data sourced from a lot of literature both print and electronic that has a connection, and analyzing data using the Content Analysis method that is analyzing the contents of the book relevant to the title. The results showed that the urgency of mental health in Islamic education is to maintain mental health, it is hoped that the creation of inner peace and happiness of the world and the hereafter is reflected in the Mahhlal Morals so that humans can fulfill their duties and responsibilities as servants and caliphs on earth and can develop all potential owned so that it can be useful for themselves, others and the environment.